Effectiveness of Family Empowerment towards Diet Compliance and Family Independence in Caring for Family Members with Diabetes Mellitus: A Systematic Review - Angga Miftakhul Nizar; Kusnanto; Lilik Herawati (Poltekkes Kemenkes Palu, 2021)
Diabetes mellitus has now become a major problem in non-communicable diseases whose prevalence continues to increase. Lack of family independence and client non-compliance with the diet program greatly affects blood sugar levels. This study needs to evaluate the effectiveness of family empowerment towards diet compliance and family independence in caring for family members with diabetes mellitus. A systematic review searched five electronic databases (Scopus, sciencedirect, pubmed, research gate, and google scholar) with the last ten years (2011-2021). The quality of the articles used in this study was assessed using the Joanna Briggs Institute Guideline. The prism protocol is also used to review each journal. We found 15 studies out of a total of 5,865 studies that discussed family empowerment in increasing family independence and dietary adherence in family members suffering from diabetes mellitus. Family empowerment is one method that is quite effective in increasing family independence and adherence to diet programs. There are six articles (40%) that state that planned behavior theory is effective in increasing family independence and dietary adherence to family members suffering from diabetes mellitus. From all the articles analyzed, there are several effective theories to empower families to change the behavior of family independence and individual diet compliance, namely the theory of planned behavior. However, this study is not strong enough to provide an assessment that family empowerment based on the theory of planned behavior and empowerment is the best way to increase independence, therefore further research is needed.